Analisis Pengelolaan Zakat, Infak, Dan Sedekah (ZIS) Untuk Meningkatkan Ekonomi Duafa (Studi Kasus di Lembaga Amil Zakat Nurul Hayat Cabang Medan ) - Nazlah Khairina (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2019)
This study aims to analyze the way LAZ Nurul Hayat collects ZIS funds and to analyze how the distribution of ZIS by Nurul Hayat in improving duafa economists, to analyze how the strategy carried out by LAZ Nurul Hayat in improving the economy of the poor. The research methodology is using the qualitative research with descriptive approach. Data collection techniques were carried out by in-depth interviews and documentation. The data analysis techniques are done by reducing, presenting data and drawing conclusions. The results of this study indicate that how to collect Zakat, Infaq, Sedekah funds is in three ways, namely amil coming to the place of muzaki, muzaki transferring funds to Nurul Hayat and the last one is muzaki coming directly to Nurul Hayat's office. Efforts in the distribution of ZIS in Nurul Hayat were carried out by direct survey of mustahik who were programmed to be given assistance, by choosing two categories, which were worthy of special assistance and worthy of assistance. The strategy carried out by Nurul Hayat is by monitoring the development of business carried out by mustahik who are given ZIS funds by monitoring and guiding if there are difficulties in developing their business.